Modelling the knowledge management processes for planning and scheduling of construction projects based on state-of-the-art technology - Bahtiar, Siti Fazreena Idayu (2012)
Construction management is an information intensive industry. In construction projects, knowledge is usually buried in unread reports and arcane filing systems, or lost because people move on, leads to wasted activity of reinventing the wheel and impaired project performance. The application of Knowledge Management (KM) has been identified to be lagging in the area of construction project. Previous developments for KM in the construction industry are focused on traditional project management philosophy of focusing on tasks. Based on high focused research on construction management by Lean practitioners and researchers it is evident that breakthrough improvements in construction can be achieved by focusing on flows. This study focuses on modelling the technology enabled KM process using a reengineered Last Planner System (LPS) that focuses on flows and Integrated Production Scheduler (IPS) process. Taking an action research approach, a case study was documented to map out the information flow and the KM mechanism. The KM process was modelled based on systematic cyclical observation and analysis. A questionnaire survey was carried out to understand the current practice of information flow management and identify the KM mechanism as well. The result revealed that currently, the construction practitioners applied the traditional approach of project management practice and there are inefficiencies of the current practice. Questionnaire result also had identified KM mechanism that currently being practiced in Planning and Scheduling (P&S) activities. Hence, a proposed system was developed to enhance the current construction management process that performs the role of KM mechanism. At the end of this study, a working model for KM in P&S was developed. The initial feedback of system evaluation on functionality, applicability and effectiveness was gained and will be used in future research work.